Pathophysiology and reproductive hormones disturbances of non-pregnant does post-challenged with Mannheimia haemolytica serotype A2 and its lipopolysaccharide endotoxin - Mat Isa, Kamarulrizal (2021)
Pneumonic mannheimiosis is a common respiratory disease occurring in goats and sheep with worldwide prevalence. It causes enormous economic losses to small ruminant farmers due to high morbidity and mortality rates, especially in young animals, and decreased productivity among flock survivors. In Malaysia, pneumonic mannheimiosis in goats is predominantly caused by Mannheimia haemolytica serotype A2, a Gram-negative bacterium belonging to the genus Mannheimia and the family Pasteurellaceae. During disease pathogenesis, the bacteria produce Lipopolysaccharide (LPS) endotoxin, one of the major virulence factors responsible for the pathophysiological effects of pneumonic mannheimiosis. Previous investigations have revealed that LPS endotoxin from certain Gram-negative bacteria such as Escherichia coli and Pasteurella multocida could adversely affect the reproductive system of female animals. However, it is unknown whether LPS endotoxin of M. haemolytica serotype A2 may also induce similar insidious effects, as most earlier studies focused primarily on the respiratory system. Moreover, there is limited information regarding the pathology of the reproductive organs and the response of reproductive hormones in female goats infected with pneumonic mannheimiosis. Therefore, this study was designed to investigate the effects of M. haemolytica serotype A2 and its LPS endotoxin on clinical responses, reproductive hormones (progesterone and oestrogen), pro-inflammatory cytokines (interleukin-1β and interleukin-6), acute-phase proteins (haptoglobin and serum amyloid A) and histopathology of reproductive organs, vital organs, and its associated lymph nodes in female goats’ model. A total of 12 clinically healthy adults, non-pregnant crossbred does, aged between 12 to 18 months, weighing approximately 25±2kg, were used in this study. They were randomly divided into three equal experimental groups (Group 1, Group 2, and Group 3) and kept in three separate pens. Does in Group 1 served as a negative control group and were given intranasally with 2 ml of sterile phosphate-buffered saline (PBS). Does in Group 2 were challenged intranasally with 2 ml of bacterial cell suspension containing 109 colony-forming unit (CFU) per ml of M. haemolytica serotype A2, while does in Group 3 were challenged intravenously with 2 ml of LPS endotoxin extracted from 109 CFU/ml of M. haemolytica serotype A2. Following the challenges, all does were closely monitored, and clinical responses were recorded daily for 60 days. Blood samples were collected serially at predetermined intervals for serological analysis using commercial ELISA kits. On the 60th day postchallenged, all does were euthanised by slaughter for macroscopic and microscopic post-mortem examinations. The results revealed that does in both challenged groups (Group 2 and Group 3) showed significant alterations (p < 0.05) in clinical responses at several time points compared to the control group. The clinical responses observed were pyrexia, tachycardia, tachypnoea, mild crackle lung sound, mild coughing, serous to mucoid nasal discharges, and mild to moderate rumen hypomotility. Analysis of serum samples demonstrated significant increases (p < 0.05) in the mean concentrations of reproductive hormones (progesterone and oestrogen), pro-inflammatory cytokines (IL-1β and IL-6), and acute-phase proteins (Hp and SAA) in both challenged groups at several time points compared to the control group. Histopathological results revealed that both challenged groups displayed significant macroscopic lesions in the lungs and microscopic lesions (p < 0.05) were observed in the ovaries, fallopian tubes, uterine horns, uterine body, lungs, liver, and its associated lymph nodes. The severity of cellular alterations ranged from normal to moderate for haemorrhage and congestion; degeneration and necrosis; inflammatory cell infiltration, and oedema. In conclusion, this study reports for the first time that pneumonic mannheimiosis caused by M. haemolytica serotype A2 is capable of inducing pathological changes in the reproductive organs and interfering with the production of reproductive hormones in non-pregnant does, where its LPS endotoxin responsible for the etiopathogenesis. These novel discoveries suggest that pneumonic mannheimiosis may potentially interfere with reproductive efficiency and predispose infected does to infertility.